Curriculum development for online teaching and learning : academics’ perspectives from a rural-based university in South Africa - Baloyi, Nhlayisi Cedrick; Malatji, Edgar Julius (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This study sought to explore academics’ perceptions of the development and delivery of curriculum for online teaching and learning in a rural-based university. Technology integration into teaching and learning in higher education is receiving more attention, thanks to the Coronavirus pandemic that has forced all facets of lives to look for alternative methods of operation instead of face-to-face contact. The pandemic saw most institutions of higher learning move their mode of curriculum delivery from face-to-face to multimodal learning using technology. This, however, was done without considering whether the existing curriculum that was accredited to be delivered face-to-face will perfectly fit into multimodal learning. The exploratory research design within the qualitative research methodology was applied in this paper. Purposive and convenience sampling techniques were applied to sample a rural university in Limpopo province of South Africa, and academics respectively. Semi-structured interviews and reflexive thematic analysis were employed for data collection and analysis for this paper. The study revealed there is a relationship between curriculum development and the mode of delivery used for teaching. Some of the academics indicated that a lack of technological skills poses a threat to adopting new technologies for teaching. In light of this, the study recommends ICT infrastructure investment and human resource capacitation for proper integration of technology for teaching and learning.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (1) (2023)
Keywords: Curriculum; Technology; Higher education; Teaching; Learning; Curriculum planning; Education, Higher; Technology -- Study and teaching